SOFSEM 2018 : theory and practice of computer science : 44th International Conference on Current Trends in Theory and Practice of Computer Science, Krems, Austria, January 29 - February 2, 2018, Proceedings /: theory and practice of computer science : 44th International Conference on Current Trends in Theory and Practice of Computer Science, Krems, Austria, January 29 - February 2, 2018, Proceedings. (2018) - Unknown
No abstract available